Utilization Of Black Tea Pulp Extract (Black Tea) As An Active Ingredient In Hand Wash Preparation - Kurniawan, Arandi Tubagus; Santoso, Joko; Purgiyanti, Purgiyanti (Sean Institute, 2025)
In the use of natural hand wash, black tea pulp (Camellia sinesis L.) contains useful active substances. The preparation helps reduce the spread of germs originating from physical contact. Extraction was carried out using maceration extraction technique. This study aims to explore the physical properties of the developed hand wash dosage formulation, containing black tea pulp extract. Using various testing parameters. The testing methods involved organoleptic test to evaluate the homogeneity properties, pH measurement to assess the acidity or basicity level, foam height measurement of the preparation and viscosity measurement to understand the flowability. In addition. Specific gravity test of hand wash preparations to determine the specific gravity that has been made so as to obtain ideal pharmaceutical preparations. Hand wash preparation of black tea pulp extract with 5%, 10%, 15% concentration. By utilizing these various parameters, the study aims to provide a comprehensive picture of the physical properties of the product, helping to identify the strengths and weaknesses of the formulation. This forms the basis for further development to improve the quality of the hand wash, with the added value of the natural extract of Black Tea Dregs.